Bariatric surgery in obese women of reproductive age improves conditions that underlie fertility and pregnancy outcomes: retrospective cohort study of UK National Bariatric Surgery Registry (NBSR) - Edison, E; Whyte, M; Van Vlymen, J; Jones, S; Gatenby, P; de Lusignan, S; Shawe, J (Springer, 2016)
Background The aims of this study are the following: to describe the female population of reproductive age having bariatric surgery in the UK, to assess the age and ethnicity of women accessing surgery, and to assess the effect of bariatric surgery on factors that underlie fertility and pregnancy outcomes. Methods Demographic details, comorbidities, and operative type of women aged 18–45 years were extracted from the National Bariatric Surgery Registry (NBSR). A comparison was made with non-operative cases (aged 18–45 and BMI ≥40 kg/m2) from the Health Survey for England (HSE, 2007–2013). Analyses were performed using “R” software. Results Data were extracted on 15,222 women from NBSR and 1073 from HSE. Women aged 18–45 comprised 53 % of operations. Non-Caucasians were under-represented in NBSR compared to HSE (10 vs 16 % respectively, p < 0.0001). The NBSR group was older than the HSE group—median 38 (IQR 32–42) vs 36 (IQR 30–41) years (Wilcoxon test p < 0.0001). Almost one third of women in NBSR had menstrual dysfunction at baseline (33.0 %). BMI fell in the first year postoperatively from 48.2 ± 8.3 to 37.4 ± 7.5 kg/m2 (t test, p < 0.001). From NBSR, in the postoperative period, the prevalence of type 2 diabetes fell by 54 %, polycystic ovarian syndrome by 15 %, and any menstrual dysfunction by 12 %. Conclusions Over half of all bariatric procedures are carried out on women of reproductive age. More work is required to provide prompt and equal access across ethnic groups. At least one in three women suffers from menstrual dysfunction at baseline. Bariatric surgery improves factors that underlie fertility and pregnancy outcomes. A prospective study is required to verify these effects.